A Model for Predicting Capacity Fade due to SEI Formation in a Commercial Graphite/LiFePO4 Cell. Issue 6 (10th March 2015) - Ekström, Henrik; Lindbergh, Göran
Abstract : An aging model for a negative graphite electrode in a lithium-ion battery, for moderate currents up to 1C, is derived and fitted to capacity fade experimental data. The predictive capabilities of the model, using only four fitted parameters, are demonstrated at both 25°C and 45°C. The model is based on a linear combination of two current contributions: one stemming from parts of the graphite particles covered by an intact microporous solid-electrolyte-interface (SEI) layer, and one contribution from parts of the particles were the SEI layer has cracked due to graphite expansion. Mixed kinetic and transport control is used to describe the electrode kinetics.